Nobody wanted to play - Hunt, Roderick (Oxford university press, 1986)
"Nobody Wanted to Play" by Roderick Hunt, part of the Oxford Reading Tree series, tells the story of Biff, Chip, Kipper, and their friends who are feeling left out and lonely when no one wants to join them in play.
Keywords: Textbook